Fatigue behaviour and BS7608 fatigue classes of steels with thermally cut holes. (January 2017) - Cicero, S.; García, T.; Álvarez, J.A.; Klimpel, A.; Bannister, A.; Martín-Meizoso, A.
Abstract: Thermal cutting includes oxy-fuel, plasma and laser cut technologies. These cutting methods generate cut surfaces and material transformations that determine the final fatigue behaviour of cut structural components. The BS7608, like most of the standards, does not provide fatigue design curves for thermally cut holes, restricting its scope to drilled or reamed holes. This limits the use of oxy-fuel, plasma and laser technologies in numerous engineering applications. This research analyses the effect of the three thermal cutting methods on the fatigue behaviour of cut holes performed on a wide range of structural steels (S355M, S460M, S690Q and S890Q). The experimental fatigue results obtained have been used to generate the corresponding BS7608 design classes, which have also been validated by comparing them to experimental data found in the literature. Graphical abstract: Highlights: Oxy-fuel, plasma and laser cut holes are not currently covered by BS7608. This work analyses the effect of oxy-fuel, plasma and laser cuts on the fatigue behaviour of cut holes. A wide range of structural steels (S355M, S460M, S690Q and S890Q) is covered. The corresponding BS7608 design classes have been obtained and validated.